Android-Based Local History Learning to Strengthen Students' Understanding of Yogyakarta Cultural Heritage - Darsono; Arif Saefudin (International journal of technology and education research, 2026)
Advances in digital technology have driven the transformation of history education through the use of more interactive and contextual Android-based media. This study aims to explore students’ experiences in using Android-based local history learning and to analyze its contribution to enhancing their understanding of Yogyakarta’s cultural heritage. The study employed a qualitative approach, involving 10th-grade students and a history teacher at a high school in the Special Region of Yogyakarta, selected through purposive sampling. Data were collected via open-ended questionnaires, in-depth interviews, and observations, and were analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that Android-based local history learning enhances students’ interest and motivation, facilitates their understanding of the history and philosophical values of Yogyakarta’s cultural heritage, and fosters a growing awareness of the need to preserve local culture. The integration of multimedia—including text, images, videos, interactive maps, and quizzes—provides a more meaningful learning experience compared to conventional teaching methods. This study contributes an Android-based local history learning model that integrates Yogyakarta’s cultural heritage as a contextual learning resource, thereby supporting the strengthening of students’ cultural identity while also promoting cultural preservation in the era of digital transformation.